1936
DOI: 10.1084/jem.63.5.703
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Synergy

Abstract: The following experiments were stimulated by our interest in the subject of "allergic irritability" (1) and in the work of Burky (2) who observed that weakly antigenic substances, for example, beef lens and ragweed pollen, provoked in rabbits marked antibody formation and hypersensitiveness when combined with staphylotoxin produced by growing staphylococci in broth containing the weak antigen. He hypothesized that this was due to the conjugation, in vitro, of the poor antigen with the powerful antigenic toxin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1937
1937
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The induction of bacterial hypersensitivity affected a much more pronounced increase in reactivity to rabbit serum. Probably similar nonspecific alterations in imimunological reactivity incident to the development of bacterial hyperseinsitivity have also been observed with respect to horse serum (Schultz (7)) and eye lens extract (Swift and Schultz (8,2)). …”
Section: Discussionmentioning
confidence: 65%
“…The induction of bacterial hypersensitivity affected a much more pronounced increase in reactivity to rabbit serum. Probably similar nonspecific alterations in imimunological reactivity incident to the development of bacterial hyperseinsitivity have also been observed with respect to horse serum (Schultz (7)) and eye lens extract (Swift and Schultz (8,2)). …”
Section: Discussionmentioning
confidence: 65%
“…One such approach was the use of toxin-antitoxin mixtures [19]. Another approach involved work with tuberculosis (TB) vaccines which demonstrated that the infl ammation induced by TB could enhance immune responses to other antigens.…”
Section: Initial Development Of Adjuvants For Toxoid Vaccines: 1920s-mentioning
confidence: 99%